#### Answer

$0$

#### Work Step by Step

RECALL:
For any real numbers $a, b,c$ and $d$,
$ad-bd+cd=(a-b+c)d$
Use the rule above to combine like terms:
$=(4-6+2)\sqrt{11}
\\=(-2+2)\sqrt{11}
\\=0\sqrt{11}
\\=0$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

$0$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.